2014 2nd International Conference on Electrical, Electronics and System Engineering (ICEESE) 2014
DOI: 10.1109/iceese.2014.7154600
|View full text |Cite
|
Sign up to set email alerts
|

Mobile robot obstacle avoidance in various type of static environments using fuzzy logic approach

Abstract: Autonomous mobile robot is a mobile robot that can move without human supervision. The use of autonomous mobile robots has increased in various fields such as in the industrial, agricultural, and military sectors. This paper presents the development of a mobile robot that uses Fuzzy Logic approach to control a robot's movement in an area cluttered with static obstacles. In the experiment presented herewith, the controller was programmed with 256 Fuzzy Logic rules and the input to the system is from an E-puck r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Fuzzy logic approach was employed in [153] to develop a controller with 256 fuzzy logic rules with environmental data collected using IR sensors. Webot Pro and MATLAB were used for the software development and simulation, respectively.…”
Section: Fuzzy Logic Path Planningmentioning
confidence: 99%
“…Fuzzy logic approach was employed in [153] to develop a controller with 256 fuzzy logic rules with environmental data collected using IR sensors. Webot Pro and MATLAB were used for the software development and simulation, respectively.…”
Section: Fuzzy Logic Path Planningmentioning
confidence: 99%
“…In the context of sensor technology, our method employs the common ultrasonic sensor for wall following task and the advanced camera sensor for detecting obstacle. Compared to [4], [7][8][9], our camera sensor offers the flexible detection of the obstacles.…”
Section: Comparison To the Existing Systemsmentioning
confidence: 99%
“…The mobile robots for avoiding obstacles were addressed in [7][8][9][10][11]. A mobile robot was operated in the warehouse for transferring the objects [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile robot's movement in a cluttered area with static obstacles was controlled via fuzzy approach and used webots simulator and Matlab software. it is indicated that webots and Matlab are suitable tools to develop and simulate mobile robot navigation [25].…”
Section: Related Workmentioning
confidence: 99%